Sintesis komposit berbasis styrofoam dan kulit kayu galam sebagai adsorben besi pada limbah cair pertambangan intan - Nugravita, Annisa Nurfadilla; Dirgahayu, Daniel; Fitriani, Rizky Aulia; Gea, Temani; Irawati, Utami (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2025)
South Kalimantan Province is well known for its abundant diamond production. However, diamond mining activities leave excavation pits filled with water that cannot be utilized due to high concentrations of heavy metals. This study aims to develop an effective method for synthesizing a composite from styrofoam-derived polystyrene and cellulose extracted from galam wood (Melaleuca cajuputi) bark as an adsorbent, characterize the obtained composite, and evaluate its adsorption capability compared to commercially activated carbon for diamond mining wastewater treatment. Cellulose was isolated from galam wood bark, while polystyrene was obtained from styrofoam. The isolated materials were then used for composite synthesis. The adsorption process was examined by analyzing the effects of contact time and adsorbent mass. The optimal masses for the composite, activated carbon, and galam wood bark powder were found to be 1 g, 7.5 g, and 5 g, respectively. After treatment, the final turbidity levels using these adsorbents were 1.82, 486, and 232 NTU, respectively, compared to an initial turbidity of 1110 NTU. Atomic Absorption Spectroscopy (AAS) results indicated that the PSS-cellulose composite reduced iron (Fe) concentration from 38.30 mg/L to 24.12 mg/L.